Study on coordination in service supply chains with incentive mechanism under quantity flexibility contracts - Yu, Hai-Hong; Liu, Nan (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2012)
Based on quantity flexibility contract, this paper constructed a pure service two-echelon structure and analyzed the service supply chain's incentive mechanism and coordination mechanism. The paper argues that in order to optimize the benefits of service supply chain, it calls for the service provider to implement incentive mechanism on service supplier, and the incentive mechanism directly affects the coordination criteria and the feasibility of coordination in service supply chain as well as the flexibility of profit distribution. The results show that service supply chains based on quantity flexibility contract can realize coordination, and has good flexibility of the profit distribution; but different from the product supply chain, service supply chain coordination is subject to related parameters from specified service supply chains such as suppliers' effort cost, demand distribution under different efforts, etc.